Individual tumor volume responses to short-course oxaliplatin-containing induction chemotherapy in locally advanced rectal cancer – Targeting the tumor for radiation sensitivity?. Issue 3 (June 2016) - Flatmark, Kjersti; Saelen, Marie G.; Hole, Knut H.; Abrahamsen, Torveig W.; Fleten, Karianne G.; Hektoen, Helga H.; Redalen, Kathrine R.; Seierstad, Therese; Dueland, Svein; Ree, Anne H.
Abstract: Background: Neoadjuvant treatment of locally advanced rectal cancer (LARC) involves chemoradiotherapy (CRT), which may cause significant toxicity, and the potential role and sequential placement of neoadjuvant chemotherapy (NACT) relative to CRT is under debate. Patients and methods: In a non-randomized study of 72 LARC patients, short-course oxaliplatin-containing NACT was administered prior to CRT. Tumor volumes were calculated from magnetic resonance images before and after NACT, and four weeks after CRT, and associations between tumor volume responses and outcome were analyzed. Additionally, the impact of oxaliplatin exposure on radiosensitivity was examined in colorectal carcinoma cell lines. Results: All tumors except one responded to NACT, with better responses in T3 than T4 cases, and 69/72 patients obtained additional tumor volume reduction after subsequent CRT. However, no associations were found between tumor volume reduction and long-term outcome. Of note, oxaliplatin-resistant cells were significantly more radiosensitive than the oxaliplatin-sensitive counterparts. Conclusions: Oxaliplatin-containing NACT led to substantial tumor volume reduction with particularly good responses in T3 cases. NACT did not impede subsequent CRT response, and experimental results rather suggested enhanced radiosensitivity in oxaliplatin-exposed cells, encouraging studies to explore the administration of NACT prior to CRT. Data are still lacking to support omitting radiation in LARC management.